2011
DOI: 10.1016/j.ajpath.2010.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 (HSP70) Is Critical for the Photoreceptor Stress Response after Retinal Detachment via Modulating Anti-Apoptotic Akt Kinase

Abstract: Photoreceptor apoptosis is a major cause of vision loss in many ocular diseases. Significant progress has been made to elucidate the molecular pathways involved in this process, yet little is known about proteins counteracting these apoptotic pathways. It is established that heat shock proteins (HSPs) function as molecular helper proteins (chaperones) by preventing protein aggregation and facilitating refolding of dysfunctional proteins, critical to the survival of all organisms. Here, we investigated the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…Kayama et al reported the role of HSP70 in the molecular interplay between pro-survival and pro-apoptotic pathways after photoreceptor stress (26). In the present study, PDT induced the overexpression of HSP70 and HSP90 (Fig.…”
Section: Hsp70 Plays a Fundamental Role In Protecting Cells Against Pdtsupporting
confidence: 62%
“…Kayama et al reported the role of HSP70 in the molecular interplay between pro-survival and pro-apoptotic pathways after photoreceptor stress (26). In the present study, PDT induced the overexpression of HSP70 and HSP90 (Fig.…”
Section: Hsp70 Plays a Fundamental Role In Protecting Cells Against Pdtsupporting
confidence: 62%
“…A previous study indicated that Hsp70 is critical for the photoreceptor stress response after retinal detachment (13), however further investigation is required to determine the mechanisms of interaction between Hsp70 and photoreceptor cell death. Hsp70 assists in denatured protein folding to repair DNA damage, transfers irreversibly damaged proteins to protein degradation system and allows cellular adaptation, which is necessary for cell survival (33), and numerous reports have demonstrated that Hsp70 has manifold anti-apoptotic effects both upstream and downstream of caspase activation (13,34,35). For example, upregulation of Hsp70 can increase the expression of the major anti-apoptotic protein Bcl-2 (36), which interferes with the release of cytochrome c, the oligomerization of apoptotic protease activating factor-1 and the activation of caspase-9, thereby preventing the aggregation of the apoptosome (37).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the precise neuroprotective mechanisms of donepezil are complex and remain controversial. Therefore, more research is required to determine the effect and mechanisms of donepezil acting on on photoreceptor cells (13). It has been demonstrated that AChE inhibitors lead to increased mRNA expression levels of heat shock protein 70 (Hsp70), resulting in enhanced cellular defenses in neurons (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that administration of geranylgeranylacetone (GGA), an acyclic polyisoprenoid, up-regulates heat-shock protein (HSP) expression and exerts protective effects on a variety of organs, such as the eye (Suemasu et al 2009;Tanito et al 2005;Kayama et al 2011), the brain (Yasuda et al 2005), neurons (Katsuno et al 2005), and the heart (Ooie et al 2001). In the retina, GGA induced both HSP72 and thioredoxin (Trx) predominantly in the retinal pigment epithelium layer (RPE) and protected photoreceptors from light damage (Tanito et al 2005).…”
Section: Introductionmentioning
confidence: 99%